Indirubin-3′-oxime as a dual-action agent: mitigating heat-induced male infertility in Drosophila melanogaster and inhibiting soluble epoxide hydrolase - Nguyen Viet Phong; Hyo-Sung Kim; Yan Zhao; Eunbyul Yeom; Seo Young Yang (Journal of Enzyme Inhibition and Medicinal Chemistry)
This study investigated the potential of the indirubin-3′-oxime (I3O) compound to mitigate temperature-induced male infertility in Drosophila melanogaster. Elevated temperatures significantly reduced egg-hatching rates, but I3O supplementation improved these rates, suggesting it can partially restore fertility under heat stress. Additionally, I3O was found to inhibit soluble epoxide hydrolase (sEH), an enzyme involved in the metabolism of epoxyeicosatrienoic acids, which are vital for reproductive health. I3O exhibited sEH inhibitions with an IC50 value of 59.74 ± 0.41 µM. Enzyme kinetics revealed that I3O acts as a non-competitive inhibitor of sEH with a Ki value of 78.88 µM. Molecular docking showed strong interactions between I3O and key residues in the allosteric regions within the sEH enzyme, with a binding affinity of −9.2 kcal/mol. These interactions were supported by 100 ns molecular dynamics simulations, which confirmed the stability of the sEH–I3O complex.